Student considerations on sustainable material selection in undergraduate interior design competitions - Catedral, Jessa Lae C.
The purpose of this study was to determine a general understanding of sustainability and enumerate the consideration on sustainable material selection in undergraduate interior design competitions all in the perspective of the students who participated in two specific competitions. Data collection was done through personal or online semi-structured interviews among the ten 10 finalists of Estilo de Vida competition and Asia Young Designer Award in 2016. Instruments such as interview guide, timeline or schedule, and a recorder or an online communication portal were used. As an exploratory study, thematic data analysis was applied to centralize recurring ideas on the datasets to generate qualitative and quantitative analysis based on the students opinions and justifications on materials chosen for the competition, as well as employing data from the respondents design entries to support the analysis. According to the findings of this study, all the student designers were able to associate sustainability as a means to alleviate the damages in the ecological environment through responsible material selection and construction techniques. The study was also able to enumerate eleven 11 considerations that make the materials sustainable according to the respondents, these considerations were: low maintenance, air purification, water conservation, material emission, energy consumption, renewable source, locality of material, embodied energy in manufacturing, recyclability, function, and durability. It was established that interior design competitions were a great venue for students to learn outside of the curriculum. Experiences in the competitions have heavily influenced the students outlook on sustainable practices not just as a means of fulfilling a criterion but also in upholding a responsibility to the environment in future applications.